2023
DOI: 10.3389/fendo.2022.1085656
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body composition, insulin resistance, and hormonal profiles in women with polycystic ovary syndrome

Abstract: ObjectiveTo investigate how body fat influences glucose metabolism and hormone profiles in women with polycystic ovary syndrome (PCOS), compared to women without PCOS.MethodsWe conducted a cross-sectional study of 166 women with PCOS and 139 age-matched control women at Peking University Third Hospital (Beijing, China) from March 2016 to December 2021. All participants underwent bioimpedance rate assessment of clinical, anthropometric, hormonal, and metabolic features. In particular, body composition parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…These results were in accordance with other studies. 22,23,29 Based on our study, it is assumed that factors other than biometrics of body composition, such as adipokines, may contribute to insulin resistance in women with PCOS.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These results were in accordance with other studies. 22,23,29 Based on our study, it is assumed that factors other than biometrics of body composition, such as adipokines, may contribute to insulin resistance in women with PCOS.…”
Section: Discussionmentioning
confidence: 89%
“…The present study used the bioimpedance method, which was indicated to be reliable in measuring body composition parameters. 22 Moreover, the heterogeneity of PCOS pathophysiology and influences of race and environment might contribute to this dissimilarity. Although body composition did not significantly differ between the two groups, fasting insulin level and HOMA-IR value were higher in women with PCOS, showing enhanced risk of glucose intolerance and insulin resistance in PCOS women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that elevated levels of several sex hormones, including LH, T and AMH, were associated with PCOS progression [ 40 , 41 ]. Our study revealed an upward trend of ApoC3 in plasma that is positively correlated with LH, T and AMH during the progression of PCOS, but had no significant relationship to those hormones in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance and central obesity are often present in patients with PCOS, features that are strongly associated with adipose tissue dysfunction [7]. Obesity is clearly related to insulin resistance, but even lean women with PCOS are prone to develop insulin resistance [8,9], affecting about 45% of women as demonstrated in a previous study by our group [10]. Obesity is also a common finding, with a reported prevalence of 30% to 60%, that affects insulin levels regardless of its effects on insulin sensitivity [6,11,12].…”
Section: Introductionmentioning
confidence: 99%